Growth and Survival Rate of The Rainbow Kuromoi Fish (Melanotaenia parva) with Addition of Green Mussle Shell in The Culture Medium - Dian Yuliyana; Mustahal Mustahal; Achmad Noerkhaerin Putra; Tutik Kadarini (JURNAL PERIKANAN DAN KELAUTAN, 2016)
The water quality management is an important factor to increase the productivity of the fish. Optimal pH in the culture medium will make the rainbow kuromoi reproduce well. In this study the green mussel shell was used as medium to increase the water quality of the culture medium. The different concentration of green mussel shell were used namely: 0 g, 30 g, 60 g 90 g, and 120 g. The results showed that the addition of green mussel shell to the culture medium has a significant effect to the culture of rainbow kuromoi fish. The addition of 120 g of green mussel shell showed the best result in pH of water culture medium at 8,2. The best alkalinity of culture medium also found in the addition of 120 g of green mussel shell at 144,76 mg/L. The addition of green mussel shell was also affected the growth fish in term of its body length, body weight, and its survival rate. The growth of its body length were: 3,46 cm (control), B: 3.57 cm, C: 3.94 cm, D: 3.96 cm, 4.17 cm. The final weigth of the control treatment was: 0,61 ± 0.01 g, B: 0.86 ± 0.02 g, C: 1.02 ± 0.05 g, D: 1.08 ± 0.05 g dan E: 1.11 ± 0.07 g, The best SR was found at addition of 120 g shell at 82,22 ± 3,85% and the lowest SR was at control treatment at 40 ± 5.77%.